An Assessment of Pollution with Volatile Organic Compounds in the Electric Arc Furnaces. (2016) - Iluţiu-Varvara, Dana-Adriana; Mârza, Carmen Maria; Aciu, Claudiu; Hădărean, Adriana; Domniţa, Florin Vasile; Sas-Boca, Ioana-Monica; Mihu, Adriana Maria
Abstract: The steelmaking in the electric arc furnace is in the category of the industrial processes with high degree of pollution because in the air environmental factor are transferred the following pollutant substances: volatile organic compounds (VOCs), particulate matter, carbon oxides, sulphur oxides, nitrogen oxides, dioxins and furans. The aim of this paper is to assess the volatile organic compounds (VOCs) emissions from steelmaking in the electric arc furnaces, in order to improve the industrial gaseous emissions management. The experimental researches were carried out on two electric arc furnaces with alkaline lining. The measurement of volatile organic compounds emissions was performed using a Mini Rae Plus Classic device. After evaluating the level of emissions, during the melting stage of charge, it results that the VOCs concentrations from electric arc furnaces depend on the degree of contamination of the charge with organic matter, paints and plastics. The reduction of volatile organic compounds emissions to the steelmaking in the electric arc furnaces may be accomplished by charge component selection and by the use of raw materials with a degree of contamination as low as possible.